Capital Market Knowledge, Return, Risk Perception, Technological Advancement, and Investment Interest in Social Media : (Case Study on Followers of the Instagram Account of @ngertisaham) - Bayu Tri Cahya; Dwi Putri Restuti; Syarif Hidayatullah; Ratih Paramita Sari (Journal of Accounting Inquiry, 2023)
Purpose: This study aims to determine and investigate the effect of capital market knowledge, return, risk perception, and technological advancement on investment interest in social media. Methodology: The present study employs a descriptive research design that utilizes quantitative methods. The study's population consisted of followers of the @ngertisaham account on Instagram. A sample of 100 respondents was collected using the Slovin formula. The data collection methodology applies a questionnaire, and next, the acquired data is processed employing the IBM SPSS Statistics version 25 software application. The data analysis technique uses a validity test, reliability test, classical assumption test, and hypothesis testing (multiple linear regression analysis, coefficient of determination, f-test, and t-test). Findings: The findings of this study show that there is only a partial relationship between capital market knowledge, technological advancement, and investment interest among Instagram followers of the @ngertisaham account. However, this relationship is not significant. In contrast, the return and risk perception variables show positive and statistically significant effects on investment interest among Instagram followers of the @ngertisaham account. Novelty: The novelty aspect of this study is using respondents of Instagram followers of the @ngertisaham account.